Pembelajaran Bahasa Arab Komunikatif-Konstruktivistik - Awaliyah Musgamy (Institut Agama Islam Negeri (IAIN) Bone, 2018)
Constructivistic-communicative Arabic learning is a renewal of learning paradigm that orients learning process to the knowledge construction through learning by doing. Hence, constructivistic-communicative Arabic learning requires students activeness to contruct their understanding towards the learning materials. The process also requires the teachers activeness to facilitate the process of knowledge construction.